1998
DOI: 10.1191/095968398670894847
|View full text |Cite
|
Sign up to set email alerts
|

Identifying forest stand types using pollen from forest hollows

Abstract: Methods of interpreting pollen assemblages in sediment were examined using surface samples from 66 small forest hollows in Michigan and Wisconsin. All canopy trees in the surrounding 50 m were measured to provide detailed information about the source vegetation of each surface pollen assemblage. Basal area of trees in each forest sample was used to classify them into six stand types: hemlock-dominated, sugar maple/hemlock mixed, sugar maple-dominated, and ash-, oak-, and pine-dominated stands. Various statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 42 publications
1
79
0
2
Order By: Relevance
“…For example at the smallest scale, Calcotte (1995) and others have demonstrated that the fossil pollen recovered from small isolated wet areas within a forest or small basin can give a stand-scale view of vegetation (Sugita 1994). In this setting, local pollen contributes about 45-50% of the pollen input to small forested hollows in mixed hardwood conifer forests, which is enough to characterize the contributions of the major plant taxa that grew within about 50-100 m of the sample point (Calcotte 1995(Calcotte , 1998Sugita 1994). Thus, pollen studies conducted in basins of differing sizes may afford an opportunity to study changes in both local and regional vegetation and the response of local vegetation to different environmental forcing factors (Schauffler and Jacobson 2002).…”
Section: Palynologymentioning
confidence: 97%
“…For example at the smallest scale, Calcotte (1995) and others have demonstrated that the fossil pollen recovered from small isolated wet areas within a forest or small basin can give a stand-scale view of vegetation (Sugita 1994). In this setting, local pollen contributes about 45-50% of the pollen input to small forested hollows in mixed hardwood conifer forests, which is enough to characterize the contributions of the major plant taxa that grew within about 50-100 m of the sample point (Calcotte 1995(Calcotte , 1998Sugita 1994). Thus, pollen studies conducted in basins of differing sizes may afford an opportunity to study changes in both local and regional vegetation and the response of local vegetation to different environmental forcing factors (Schauffler and Jacobson 2002).…”
Section: Palynologymentioning
confidence: 97%
“…However, because of uncertainties in pollen dispersal and deposition such as pollen production, dispersal ability and basin size, the pollen assemblage does not necessarily correspond the vegetation composition (Davis & Goodlett 1960;Whitehead & Tan 1969;Kennedy et al 2005). Thus, analysing modern pollenÀvegetation relationships has been one of the most effective ways to interpret fossil pollen data (Webb et al 1981;Bradshaw & Webb 1985;Calcote 1998;Wilmshurst & McGlone 2005;Xu et al 2005). The present approach is based on the assumption that the same vegetation types have the same pollen assemblage, provided that the vegetation composition and distribution are the same.…”
Section: Introductionmentioning
confidence: 94%
“…In small sedimentary basins under a closed canopy, however, the pollen produced by nearby trees growing (local vegetation) is well represented (Chen, 1988;Sugita, 1994), but the information may not be representative of the larger forested area. Numerous palaeo-ecological investigations have used small forest hollows to study stand-level vegetation changes over centennial to millennial timescales (Calcotte, 1998;Parshall and Calcote, 2001 Closed depressions (CD) are common features of many oakbeech-hornbeam forests in the low altitudes of northeastern France, Germany (Barth et al, 2001), Luxembourg (Herault and Thoen, 2008) and Belgium (Gillijns et al, 2005;Vanwalleghem et al, 2006aVanwalleghem et al, , 2006bVanwalleghem et al, , 2008. In these small (10-30 m in diameter) closed wetlands, mostly supplied by rainwater, pollen grains are trapped in the sediment perfectly preserved (Etienne et al, 2010;Hannon et al, 2000;Lindbladh and Bradshaw, 1995;Ruffaldi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%